A Quantitative Synthesis of Intervention Research Published in Flagship EBD Journals: 2010 to 2019. (November 2021) - Garwood, Justin D.; Peltier, Corey; Sinclair, Tracy; Eisel, Heather; McKenna, John W.; Vannest, Kimberly J.
Students with emotional and behavioral disorders (EBDs) could be considered some of the most challenging students to serve in schools. The need for effective interventions for these students is ever-present. To design and implement empirical studies to better inform the field of EBDs, researchers must have a firm understanding of the most up-to-date intervention literature. The purpose of this targeted quantitative synthesis is to create such a knowledge base for the field of EBDs. Results from 55 studies indicate a declining focus on intervention research for students with EBDs in the last 10 years (2010–2019). Of the intervention research available, the quality (40% did not meet What Works Clearinghouse standards) and effectiveness on student outcomes across academic, behavioral, and social skills domains was variable (between-case standardized mean difference [BC-SMD] = 0.13–8.26, Hedges' g = −0.30 to 1.29). Future directions for the field of EBDs are included.